Recombinant Adeno-Associated Virus Serotype 6 (rAAV6) Potently and Preferentially Transduces Rat Astrocytes In vitro and In vivo - Schober, Alexandra L.; Gagarkin, Dmitriy A.; Chen, Ying; Gao, Guangping; Jacobson, Lauren; Mongin, Alexander A. (Frontiers in Cellular Neuroscience, 2016)
Recombinant adeno-associated virus vectors are an increasingly popular tool for gene delivery to the CNS because of their non-pathological nature, low immunogenicity, and ability to stably transduce dividing and non-dividing cells. One of the limitations of rAAVs is their preferential tropism for neuronal cells. Glial cells, specifically astrocytes, appear to be infected at low rates. To overcome this limitation, previous studies utilized rAAVs with astrocyte-specific promoters or assorted rAAV serotypes and pseudotypes with purported selectivity for astrocytes. Yet, the reported glial infection rates are not consistent from study to study. In the present work, we tested seven commercially available recombinant serotypes– rAAV1, 2, and 5 through 9, for their ability to transduce primary rat astrocytes [visualized via viral expression of green fluorescent protein (GFP)]. In cell cultures, rAAV6 consistently demonstrated the highest infection rates, while rAAV2 showed astrocytic transduction in some, but not all, of the tested viral batches. To verify that all rAAV constructs utilized by us were viable and effective, we confirmed high infectivity rates in retinal pigmented epithelial cells (ARPE-19), which are known to be transduced by numerous rAAV serotypes. Based on the in vitro results, we next tested the cell type tropism of rAAV6 and rAAV2 in vivo, which were both injected in the barrel cortex at approximately equal doses. Three weeks later, the brains were sectioned and immunostained for viral GFP and the neuronal marker NeuN or the astrocytic marker GFAP. We found that rAAV6 strongly and preferentially transduced astrocytes (>90% of cells in the virus-infected areas), but not neurons (∼10% infection rate). On the contrary, rAAV2 preferentially infected neurons (∼65%), but not astrocytes (∼20%). Overall, our results suggest that rAAV6 can be used as a tool for manipulating gene expression (either delivery or knockdown) in rat astrocytes in vivo.